O carnaval de Ouro Preto: mercado e tradição (1980-2011) - Sarah Teixeira Soutto Mayor (2012)
The present works goal is to comprehend the main transformations of carnival in the city of Ouro Preto related specially to the marketing initiatives perceived over these three decades and to the speeches related to the idea of tradition, in a period between 1980 and 2011. The choice of the research temporality has observed specific events in the city Ouro Preto, such as its promotion to Worlds Cultural Heritage in 1980, and a broader context of insertion of the party as the consolidation of the leisure and entertainment industries in Brazil in the 1990s. To reach the proposed goal, a literature search was performed through the dialogue with theoretical references that address key issues for understanding the object, and also a documentary research. This last one counted mainly on the study of two newspapers: the Estado de Minas, chosen due to its representation in the scenario of Minas Gerais, and the O Liberal, elected for being one of the main media of Ouro Pretos recent history. This work was divided in three chapters, noting important events in the citys carnival that served as landmarks to consider the changes in the party. From early 1980 to the year 2011, significant changes occurred in the structure of carnival and in the ways it was published by the papers. From a carnival strongly built by the local population, experienced in the streets of the city and with little media expression in the early years of the research, the party in Ouro Preto became, in 2000, a flagship of the carnival party publication in Minas Gerais. During the three decades surveyed, the private investments in shaping and disseminating the party grew considerably; the promotion of tourism through the party gained a lot of strength, resulting in the need for new forms of organization and dissemination. Among various manifestations created or maintained in the temporality studied, such as the electrical window, the erotic window, the samba schools and the ludicrous blocks (groups) as Zé Pereira dos Lacaios and the Bandalheira a new format for the party emerged in the last decade. With the initial justification of protecting the heritage and offering security to the revelers, the City came up with big concerts that took place in locations that were far away from the historical center, culminating in the creation of the Espaço Folia in 2006, a proper area for larger events, closed and with an entrance fee charged in the form of an abadá (a special type of shirt). This fact contributed to the consolidation of the carnival culture held in the students houses as the main symbol of the party in the city, conveyed as one of its most authentic traditions. It was noticed, through the sources, a strong intention of making Ouro Pretos the main carnival in Minas Gerais and highlighting it among the other parties of the Brazilian interior. In this process, the idea of tradition, first linked to a notion of the age of the manifestations, intrinsic in the very meaning of the existence of the party, starts to serve to three main functions: justification of the changes; a link between a global market that was beginning to consolidate itself in the party and the past that legitimized it; differential of a carnival that became a product. Therefore, we can conclude that the idea of tradition was essential for the perceived changes in the citys carnival, precisely (and paradoxically) by the immutability conferred to the past and by some consensus that tradition is not discussed.